Practical breast pathology - Tot, Tibor; Tabár, László; Dean, Peter B (Thieme, 2002)
Aimed at general pathologists who may not be familiar with breast examinations, this book correlates breast pathology and mammography. It provides all the basic facts needed for pathologic examinations. A strong emphasis is placed on the \"teamwork\" philosophy, teaching specialists from different fields how to function together. It provides information on understanding the connection between radiologic appearance and the underlying pathology. Topics covered include: hyperplastic changes; benign and malignant lesions; invasive breast carcinoma; preoperative diagnostic criteria; and more. It is aimed at all radiologists, pathologists, surgeons and oncologists involved in breast cancer detection.
Keywords: patologie; prsy; endokrinologie; Breast Neoplasms; Breast; Breast Diseases; nádory prsu; nemoci prsů; histologie